Effects of commercial pectin on the quality of lemon (Citrus limon var.Ponderosa) jelly - Palacpac, Jojie Marie Jonota (2002.)
Three formulations of lemon jelly were prepared with varying levels of pectin.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Lemon